Modeling diagnostics of trioxide dialuminum content in gas-aerosol medium; Proceedings of SPIE; Vol. 10035 : Atmospheric and Ocean Optics: Atmospheric Physics - Voytsekhovskaya O. K. Olga Kuzminichna; Shefer O. V. Olga Vladimirovna; Kashirsky (Kashirskii) D. E. Danila Evgenjevich; Loskutov V. V. Vitaliy Valerevich; Egorov O. V. Oleg Vladimirovich (2016, 2016)
Title screen